Platelet transcription factors license the pro-inflammatory cytokine response of human monocytes - Ibrahim Hawwari; Lukas Rossnagel; Nathalia Rosero; Salie Maasewerd; Matilde B Vasconcelos; Marius Jentzsch; Agnieszka Demczuk; Lino L Teichmann; Lisa Meffert; Damien Bertheloot; Lucas S Ribeiro; Sebastian Kallabis; et al. (EMBO Molecular Medicine, 2024)
Abstract In humans, blood Classical CD14+ monocytes contribute to host defense by secreting large amounts of pro-inflammatory cytokines. Their aberrant activity causes hyper-inflammation and life-threatening cytokine storms, while dysfunctional monocytes are associated with ‘immunoparalysis’, a state of immune hypo responsiveness and reduced pro-inflammatory gene expression, predisposing individuals to opportunistic infections. Understanding how monocyte functions are regulated is critical to prevent these harmful outcomes. We reveal platelets’ vital role in the pro-inflammatory cytokine responses of human monocytes. Naturally low platelet counts in patients with immune thrombocytopenia or removal of platelets from healthy monocytes result in monocyte immunoparalysis, marked by impaired cytokine response to immune challenge and weakened host defense transcriptional programs. Remarkably, supplementing monocytes with fresh platelets reverses these conditions. We discovered that platelets serve as reservoirs of key cytokine transcription regulators, such as NF-κB and MAPK p38, and pinpointed the enrichment of platelet NF-κB2 in human monocytes by proteomics. Platelets proportionally restore impaired cytokine production in human monocytes lacking MAPK p38α, NF-κB p65, and NF-κB2. We uncovered a vesicle-mediated platelet-monocyte-propagation of inflammatory transcription regulators, positioning platelets as central checkpoints in monocyte inflammation.